Bioadhesive hybrid system of niosomes and pH sensitive in situ gel for itraconazole ocular delivery: Dual approach for efficient treatment of fungal infections - Mohamed M. Badran; Areej Alsubaie; Mounir M. Salem Bekhit; Abdullah H. Alomrani; Aliyah Almomen; Mohamed Abbas Ibrahim; Doaa Hasan Alshora (Saudi Pharmaceutical Journal)
Itraconazole (ITZ) is a highly effective antifungal agent. However, its oral application is associated with systemic toxicity and poor topical use. The present study aims to improve the antifungal activity of ITZ by loading it into bioadhesive niosomes. This approach is considered to enhance the ocular permeation of ITZ, thereby boosting its efficacy against fungal infections. Therefore, it was encapsulated into niosomes (F1) and subsequently coated with hyaluronic acid (HA; F2), chitosan (CS; F3), or a bilayer of CS/HA (F4). In addition, they were further incorporated into pH-sensitive in situ gels. This dual approach is expected to increase the amount of corneal-permeated ITZ, facilitating more effective management of ocular fungal infection.Firstly, the niosomes were prepared by hydrating proniosomes using span 60, cholesterol, and phospholipid. ITZ-niosomes showed an increase in vesicle size from 165.5 ± 3.4 (F1) to 378.2 ± 7.2 nm (F3). The zeta potential varied within −20.9 ± 2.1 (F1), −29.5 ± 3.1 (F2), 32.3 ± 1.9 (F3), and 22.6 ± 1.3 mV (F4). The high EE% values ranged from 78.1 ± 2.2 % to 86.6 ± 2.9 %. Regarding ITZ release, F1 demonstrated a high release profile, whereas bioadhesive niosomes showed sustained release patterns. Furthermore, in situ gels containing niosomes displayed excellent gelling capacity and viscosity. Remarkably, F3 laden-in situ gels (F3-ISG) demonstrated the highest ex vivo corneal permeability of ITZ and antifungal activity with a safety effect. These results indicate that F3-ISG presents a promising strategy for boosting the ocular delivery of ITZ, that could help in treating ocular fungal infections.